2004
DOI: 10.1002/poc.736
|View full text |Cite
|
Sign up to set email alerts
|

1,3,2‐Dioxaborines as potential components in advanced materials—a theoretical study on electron affinity

Abstract: Abstract1,3,2‐Dioxaborines with fluorine and other substituents at boron were calculated by first‐principles methods based on density functional theory (DFT: B3‐LYP) or many‐body perturbation theory at the second order [MBPT(2): MP2]. 1,3,2‐Dioxaborines are derivatives of 1,3‐dicarbonyl compounds also known as 1,3‐diketoborates. According to quantum chemical calculations, 2,2‐difluoro‐1,3,2‐dioxaborines are of puckered structure with a low barrier to inversion. The calculated charge distribution does not refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 91 publications
2
29
0
1
Order By: Relevance
“…This trend confirms the relaxation toward a solvent‐equilibrated singlet excited state with a charge‐transfer character and shows that the excited‐state dipole moment is larger than the ground‐state one. This behavior is in agreement with what was observed for other curcuminoid boron difluoride compounds and is related to the strong electron‐withdrawing effect of the central difluoro dioxaborine chelate . These data evidence the strong charge transfer character of the curcuminoid dyes …”
Section: Resultssupporting
confidence: 91%
“…This trend confirms the relaxation toward a solvent‐equilibrated singlet excited state with a charge‐transfer character and shows that the excited‐state dipole moment is larger than the ground‐state one. This behavior is in agreement with what was observed for other curcuminoid boron difluoride compounds and is related to the strong electron‐withdrawing effect of the central difluoro dioxaborine chelate . These data evidence the strong charge transfer character of the curcuminoid dyes …”
Section: Resultssupporting
confidence: 91%
“…Hales et al [91], I. Kurdyukova et al [92,93] . Theoretical consideration of the electron structure of dioxaborine anionic dyes was performed by J. Fabian and H. Hartmann [94].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Their optical [1][2][3][4][5][6][7][8][9][10][11] and electrochemical [11][12][13][14][15][16] properties have been described in previous studies and it has been shown that they can be used as versatile uorophores, 1-5 electron acceptors 17,18 in one-electron transfer processes 19 or in chargetransport materials in both organic eld effect transistors and organic light emitting diodes. [20][21][22][23][24][25] One-electron reduction proceeds via the formation of a radical anion where the unpaired electron is delocalized on the p-system of the boroncontaining six-membered chelate ring, as demonstrated by electron paramagnetic resonance studies.…”
Section: Introductionmentioning
confidence: 99%